Oral health of Australian children: The National Child Oral Health Study 2012-14 - G. Do, Loc; John Spencer, A. (University of Adelaide Press, 2016)
"This collaborative work provides a detailed snapshot of child oral health in Australia. In doing so, it describes the levels of dental caries and its components, dental fluorosis and other oral health conditions and how they vary by social characteristics. It also describes protective factors such as toothbrushing, the use of fluoridated toothpastes and making dental visits. The 2012-14 National Child Oral Health Survey (NCOHS) was a cross-sectional study of the child population aged 5 to 14 years in Australia. A total of 24,664 children from 841 participating schools completed the study. The study sample was selected in a complex multistage, stratified sampling design. Sophisticated weighting procedure was employed to adjust for variations in probabilities of selection and response rates. Therefore, this report presents estimates as representative of child oral health in Australia. Information was collected via a parental questionnaire and a detailed dental examination by trained dental professionals. Despite some improvement, child oral health has remained a significant population health issue in Australia in the 21st Century. The evidence described in this book has pointed to substantial social patterning of oral health status, dental service use and dental and general health behaviours among Australian children. The identification of the numerous factors and the relation between them at an individual child, family, school and community level poses both difficulties and opportunities for programs to make improvements to and reduce social inequalities in child oral health."